Cross-sectional associations between domain-specific sitting time and other lifestyle health behaviours: the Stormont study. (3rd August 2021) - Kettle, Victoria E; Hamer, Mark; Munir, Fehmidah; Houdmont, Jonathan; Wilson, Kelly; Kerr, Robert; Addley, Ken; Sherar, Lauren B; Clemes, Stacy A
Abstract: Background: There is a dearth of literature on how different domains of sitting time relate to other health behaviours. Therefore, this study aimed to explore these associations in a sample of office workers. Methods: 7170 Northern Irish Civil Servants completed an online survey which included information on workday and non-workday sitting time in five domains (travel, work, TV, computer-use, leisure-time), physical activity, fruit and vegetable intake, alcohol consumption and cigarette smoking. An unhealthy behaviour score was calculated by summing the number of health behaviours which did not meet the current guidelines. Multinomial regressions examined associations between unhealthy behaviour score and each domain of sitting time. Results: ≥7 hours sitting at work and ≥2 hours TV viewing on a workday both more than doubled the odds of partaking in ≥3 unhealthy behaviours [Odds ratio, OR = 2.03, 95% CI, (1.59–2.61); OR = 2.19 (1.71–2.80)] and ≥3 hours of TV viewing on a non-workday nearly tripled the odds [OR = 2.96 (2.32–3.77)]. Conclusions: High sitting time at work and TV viewing on a workday and non-workday are associated with increased odds of partaking in multiple unhealthy behaviours. Interventions need to focus on these domains and public health policy should consider sitting time as an important health behaviour.